Juventude universitária e seus rumos à profissionalização : caminhos que se constroem - Sacramento, Hellen Rejane dos Santos (2014)
This work presents analyses which punctuate the relationship-work-education and youth as ´ settles ´ for academics linked to the course of pedagogy of the Universidade Federal de Sergipe (UFS). Vocational perspectives are presented and ´construct´ of the subjects as students and workers who is based on contributions from authors such as Maria Helena Abramo, MaríliaSpósito, Machado Pais, Alain Coulon that guiding discussions about youth in Brazil, Portugal and France. Contributions that signaling distinct ways of identifying, building and youth experiences enjoyed in three chapters to understand possible meanings of being young and industrious, University paths that have been drawn or not have been planned in the set of experiences that are (or have been) subjected the young investigated in these interviews. The search is to explore aspects of living at graduation, and future propositions from personal experience of the investigated in both universes elected as a research center, as the people build their academic and professional identity by establishing relationship with these two fields, realizing their movement, their experience in doing the work and the course. Search exposure is as follows: chapter I is about the youth vis-à-vis social, perspectives around the theme, the understanding of youth and troubles that tend to surround them. Chapter II scores about logical and challenges established by the market despite offers, demands of employability and binding. Chapter III brings possible reflections related to graduation as a likely way to professional career ways, structuring elements of the course of Pedagogy, curriculum, training composition perpetrated as a way to better understand their requirements to the students and their progress in understanding of the language of the subject.